Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Larrea Thomas, Lucas Nicolas (2019)
The current report contemplates a strategic proposal to the problematic that Harvard Business School’s case study named “Camposol” puts forward. The case study is set in 2016, in a context where the company Camposol has to decide between sustaining the growth they have experienced or choosing to reorganize internally. The company has grown quickly thanks to a rapidly growing market that is becoming increasingly competitive, while at the same time it must resolve its weaknesses and shortcomings in order to seize afterwards the growing opportunities at hand, with a well-rounded and established internal structure. This study’s methodology will begin by setting up a diagnosis both internal and external to the firm. This will allow acknowledgment of the conditions in which the company must operate, in order to develop afterwards the appropriate strategies it should pursue. The analysis will end by setting different measurement and control tools like a strategic control map and a balance scorecard.